Controlling untuk Menilai Hasil Pekerjaan dan Evaluasi dalam Perspektif Islam - Sabariah, Liena Marliana; Lokawati, Mara Indah; Sabila, Nurina Wulan; Ramdhan, Dadan F (Melati Institute, 2024)
This article discusses the controlling function in management with an Islamic approach. The research method used is a literature study with descriptive analysis of primary sources in the Qur'an, hadith, and Islamic management and education literature. This research aims to identify the concept of controlling in the Islamic perspective and its application in Islamic education. The results show that controlling in Islam includes not only evaluation of work results but also spiritual responsibility. The discussion outlines the implementation of Islamic values-based controlling that involves performance evaluation, comparison with standards, and corrective action that takes into account the moral and spiritual dimensions. This implementation can increase blessings and effectiveness in Islamic educational institutions.